Inherited defects of thyroid hormone metabolism - Dumitrescu, A. M. (2011)
Intracellular metabolism of thyroid hormone and availability of the active hormone, triiodothyronine, is regulated by three selenoprotein iodothyronine deiodinases (Ds). While acquired changes in D activities are common, inherited defects in humans have not been identified. Selenium (Se) is an essential trace element required for the biosynthesis of selenoproteins, and selenocysteine insertion sequence (SECIS) binding protein 2 (SBP2) represents a key trans-acting factor for the co-translational insertion of selenocysteine into selenoproteins. In 2005 we reported the first mutations in the SBP2 gene in two families in which the probands presented with transient growth retardation associated with abnormal thyroid function tests, low triiodothyronine (T(3)), high thyroxine (T(4)) and reverse T(3), and slightly elevated thyrotropin. Affected children were either homozygous or compound heterozygous for SBP2 gene mutations and the relatively mild phenotype was due to partial SBP2 deficiency, affecting the expression of a subset of selenoproteins. In vivo studies of these subjects have explored the effects of Se and thyroid hormone supplementation. In vitro experiments have provided new insights into the effect of SBP2 mutations. A broader and more complex phenotype was brought to light by the subsequent identification of three new cases from different families with SBP2 gene mutations. These mutations caused a severe SBP2 deficiency resulting in reduced synthesis of most of the 25 known human selenoproteins. Here we summarize the clinical presentation of SBP2 mutations, their effect on SBP2 function and downstream consequences for selenoprotein synthesis and function.